The Development of Writing Skills through Conceptual Writing - Akinkurolere, Susan Olajoke; Mohammed, Maryam (Islamic University Multidisciplinary Journal, 2019)
The study was to examine the development of writing skills through conceptual writing among English language in Kampala District Uganda. Specifically, the study investigated the effect, significance and role essay writing on development of writing skills among 145 students in the same schools in Kampala, which were selected using purposive and stratified random sampling strategies. There were pre-intervention and post-intervention tests as data collection instruments, which were analysed using frequencies, percentages and arithmetic mean. The main findings were that, generally, the level of English writing skills was relatively low among English language students in secondary schools of the Division because the students had not mastered the art of conceptual writing. It was concluded that essay writing, as potential conceptual writing education strategies, were significantly predictive but not practically-oriented. It was, therefore, recommended for better effectiveness in English writing, a lot more should be done to improve essay writing education. Such improvements should be the collective responsibility of all stakeholders in education.
Keywords: Schools; Writing; Development; Language Skills; English Language